Disseminating health research to public health policy-makers and practitioners: a survey of source, message content and delivery modality preferences - Sam McCrabb; Alix Hall; Andrew Milat; Adrian Bauman; Rebecca Hodder; Kaitlin Mooney; Emily Webb; Courtney Barnes; Serene Yoong; Rachel Sutherland; Luke Wolfenden (BMC, 2023)
Abstract Background Understanding the views of policy-makers and practitioners regarding how best to communicate research evidence is important to support research use in their decision-making. Aim To quantify and describe public health policy-makers and practitioners' views regarding the source, content and form of messages describing public health research findings to inform their decision-making. We also sought to examine differences in preferences between public health policy-makers and practitioners. Methods A cross sectional, value-weighting survey of policy-makers and practitioners was conducted. Participants were asked to allocate a proportion of 100 points across different (i) sources of research evidence, (ii) message content and (iii) the form in which evidence is presented. Points were allocated based on their rating of influence, usefulness and preference when making decisions about health policy or practice. Results A total of 186 survey responses were received from 90 policy-makers and 96 practitioners. Researchers and government department agencies were the most influential source of research evidence based on mean allocation of points, followed by knowledge brokers, professional peers and associations. Mean point allocation for perceived usefulness of message content was highest for simple summary of key findings and implications, and then evidence-based recommendations and data and statistical summaries. Finally, based on mean scores, policy-makers and practitioners preferred to receive research evidence in the form of peer-reviewed publications, reports, evidence briefs and plain language summaries. There were few differences in scores between policy-makers and practitioners across source, message content or form assessments or those with experience in different behavioural areas. Conclusions The findings should provide a basis for the future development and optimization of dissemination strategies to this important stakeholder group.